Air Quality Management in Bosnia and Herzegovina - World Bank (World Bank, Washington, DC, 2019)
Cities in Bosnia and Herzegovina (BiH) experience high ambient concentrations of health-damaging fine particulate air pollution in Europe. This report is one in a series of three reports on air quality management in BiH, Kosovo, and North Macedonia. This report examines the nature and magnitude of ambient air pollution (AAP) in BiH. It provides estimates of the health burden, and economic cost associated with the health impacts, of AAP, that is, fine particulate matter (PM2.5) in BiH. It also provides an analysis of the impacts of various sources of PM2.5 emissions on ambient air quality in BiH at a country level. The institutional and policy framework for air quality management (AQM) in the country is examined, including contributions of other development institutions in supporting BiH's efforts to address air pollution. Furthermore, this report presents experiences of selected countries that have applied different policy, investment, and technical interventions for air pollution, prevention, reduction, and abatement. Finally, it provides recommendations for reducing air pollution in BiH. Cities in Bosnia and Herzegovina (BiH) experience high ambient concentrations of health-damaging fine particulate air pollution in Europe. This report is one in a series of three reports on air quality management in BiH, Kosovo, and North Macedonia. This report examines the nature and magnitude of ambient air pollution (AAP) in BiH. It provides estimates of the health burden, and economic cost associated with the health impacts, of AAP, that is, fine particulate matter (PM2.5) in BiH. It also provides an analysis of the impacts of various sources of PM2.5 emissions on ambient air quality in BiH at a country level. The institutional and policy framework for air quality management (AQM) in the country is examined, including contributions of other development institutions in supporting BiH's efforts to address air pollution. Furthermore, this report presents experiences of selected countries that have applied different policy, investment, and technical interventions for air pollution, prevention, reduction, and abatement. Finally, it provides recommendations for reducing air pollution in BiH.